AB0231 Elevation of Serum Matrix Metalloproteinase-3 in A Group of Rheumatoid Arthritis Algerian Patients. (10th June 2014) - Fodil, D.; Salah, S.S.; Benidir, M.; Adjabi, S.; Abbadi, M.C.; Attal, N.; Bayou, M.; Mostefai, S.
Abstract : Background: Matrix metalloproteinase-3 (MMP-3) is a protease induced by inflammatory cytokines in rheumatoid synovium and degrades a number of extracellular matrix components of cartilage and bone. Its central role in rheumatoid joint destruction was especially highlighted from both pathophysiological and clinical studies. In addition, serum MMP-3 level is a clinically useful maker for predicting joint destruction and for disease activity in rheumatoid arthritis (RA). Objectives: The aim of our study is to evaluate the serum matrix metalloproteinase 3 (MMP-3) levels in a group of algerian patients with early and advanced rheumatoid arthritis (RA) compared to healthy subjects. Methods: The study group consisted of 50 patients with RA, including 81.6% women, mean age 45, 0±15, 0 years, mean duration 4, 3±4, 2 years, Forty healthy subjects served as a control group (71.4% women, mean age 33, 0±13, 0 years). Analysis of serum concentrations of MMP-3 was based on a quantitative sandwich ELISA (Aeskulisa DF MMP-3, Aesku.Diagnostics, Wendelsheim, Germany). A cut-off point of 120 ng/ml (men) and 60 ng/ml (women) was used for MMP-3 positive/negative categorization. Results: First of all, 61, 3% of patients were rheumatoid factor (RF)-positive and 93, 8% anti-CCP positive. MMP-3 is significantly higher in sera of RA patients (Mean value: 175, 8±178, 2 ng/ml) than in those of control group (Mean value: 23, 0±17, 8 ng/ml) (p<0, 001). The mean value in female and male patients was 161, 9±174, 7 ng/ml and 237, 6±203, 8 ng/ml respectively. Further, MMP-3 is higher (188, 1±183, 7 ng/ml) in sera of patients with early (<2 years duration) than advanced disease (between 3 and 8 years duration) (Mean value: 154, 0±153, 1 ng/ml) (p<0, 05). Interestingly, there is no statistically significant difference between RF-positive patients and RF-negative patients concerning MMP-3 concentration (180, 2±196, 6 ng/ml vs. 183, 3±201, 4 ng/ml respectively). Conclusions: In conclusion, patients with RA are characterized by high serum concentrations of MMP-3, particularly in early stages for both female and male affected patients regardless for RF positiviy. Serum concentration of MMP-3 is a useful marker of inflammation in the early stage of RA. References: Tchetverikov, I. et al. (2003) Matrix metalloproteinases-3, -8, -9 as markers of disease activity and joint damage progression in early rheumatoid arthritis. Ann. Rheum. Dis. 62, 1094-1099. Shinozaki, M. et al. (2007) Elevation of serum matrix metalloproteinase-3 as a predictive marker for the long-term disability of rheumatoid arthritis patients in a prospective observational cohort IORRA. Mod. Rheumatol. 17, 403-408. Fiedorczyk, M. et al. (2006) Serum matrix metalloproteinases and tissue inhibitors of metalloproteinases in patients with early rheumatoid arthritis. J. Rheumatol. 33, 1523-1529. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.6019